THE PERFORMANCE OPTIMIZATION OF GENERAL CRIMINAL UNIT I IN DISCLOSING THE CRIMINAL ACTS OF THE WEIGHTING TO INCREASE CRIME CLEARANCE IN THE JURISDICTION OF THE KENDAL POLICE - MUHAMMAD FITRIANOR (Indonesian Journal of Police Studies, 2022)
Indonesia is a state of law which means that all aspects of the life of the nation and state are based on law. The life of the nation and state is inseparable from the social life of the pluralistic Indonesian society. A pluralistic society raises the problem of socio-economic inequality. Socio-economic imbalances have an impact on poverty. Poverty triggers the emergence of street crimes such as theft by weight. This study aims to examine the implementation of the disclosure of the crime of theft by weight, the influencing factors and optimization efforts to increase the Crime Clearance of the Kendal Police. The research method uses a qualitative approach with the type of field research. Sources of data obtained from primary and secondary data. The data collection techniques used interviews, observation, and document review. The research location is Unit I General Crimes of the Kendal Police Satreskrim. The validity of the data using the triangulation method. Data analysis with interactive models through data reduction, data presentation, and conclusions and data verification. The results show that the disclosure of the crime of theft with weights refers to the standards of planning, organizing, actuating and controlling the Criminal Investigation Unit number 1,2,3 and 4 of 2014. Several influencing factors are the quantity and quality of human resources, budget, infrastructure, crime scene information and status quo. Efforts to optimize disclosure of theft by weighting utilize Kring Investigation as a quick response and reference in developing information networks. In conclusion, the implementation of the disclosure of the crime of theft by weighting is guided by existing regulations, but there are factors that influence it. Suggestions for optimizing Unit I by carrying out activities based on SOPs, complementing the shortcomings of Unit I, and improving the quality of human resources.